Kewirausahaan (Entrepreneurship) dalam Perspektif Qur'an dan Hadits - Burhanuddin Ridlwan; Mahmud Fauzi; Ali Said (Menara Tebuireng, 2016)
Entrepreneurship is a theme that remains attractively to be studied or researched, moreover the viewpoint of the Qur'an and the Hadith, as a major source of Islamic teachings. A Muslim will still need to understand and deepen it. Thus, the research aims have scientific assessment results which can be used as the basis for a Muslim in running the entrepreneurship. Independence of life and success generated by entrepreneurial activity, which also means by increased welfare, become meaningless without increasing faith and devotion. The method used in this research is literary study, it is a study carried out to solve a problem which is based on in-depth review of critical and relevant to library materials in accordance with the focus of the study. The focuses researches are: Definition of entrepreneurship, entrepreneurship in general perspective, and the perspective of entrepreneurship in the Quran and hadith. All the verses and hadiths pertaining to entrepreneurial above require examination or in-depth study of reference books in the field of Quran and tafsir and hadith and syarakh (additional explanation), written by many of the scholars, we restudy, analyze, and interpret related to the newest conditions